Kokology : the game of self-discovery - Nagao, Tadahiko; Saito, Isamu (New York : A Fireside Book, Simon & Schuster, 2000)
A collection of psychological games and quizzes that reveal personality traits and insights about how people think, feel, and behave.
Keywords: Personality tests -- Miscellanea; Self-perception. -- Testing -- Miscellanea; Parapsychology -- Testing -- Miscellanea